Structural change and gender sectoral segregation in sub-Saharan African countries - Izaskun Zuazu (Journal of International Development, 2024)
Structural change has long been at the core of economic development debates. However, the gender implications of structural change are still largely unexplored. This paper helps to fill this gap by analysing the role of structural change in the gender distribution of sectoral employment in sub-Saharan African countries. I employ aggregate and disaggregate measures of gender sectoral segregation in employment, which measure the difference between the gender distribution across sectors with respect to the overall participation of women and men in the labour market. I build a panel database consisting of 10 sectors and 11 countries during 1960–2010. Fixed effects and instrumental variables' regression models show a significant, nonlinear link between labour productivity and gender segregation. Increasing labour productivity depresses gender segregation at initial phases of structural change. However, further productivity gains beyond a certain threshold of sectoral development increases gender segregation. Country-industry panel data models complement the analysis showing that relative labour productivity has a nonlinear impact in gender segregation: Initial increases in relative productivity increases feminization but further relative productivity gains foster the masculinization of sectors. The estimates suggest that manufacturing, utilities, construction, business, and government services are key to correct gender biases in employment along the process of structural change.
Keywords: 300; association index; dissimilarity index; gender sectoral segregation; instrumental variables; structural change